Structured Interview Matrix (SIM) Facilitators’ Guide - O'Sullivan, Tracey; Tracey, Shannon; Corneil, Wayne (Université d'Ottawa | University of Ottawa, 2022)
The Structured Interview Matrix (SIM) is a participatory method for consulting stakeholders and creating opportunities for networking. This guide provides an overview of how to plan and conduct an in-person SIM session, as well as a protocol for using the method virtually.
Keywords: Structured Interview Matrix; SIM; Focus group; Online focus group; Facilitation; Stakeholder engagement